Defining the suitability for nectar production, bee bread and honeydew in managed forests (Trentino, Italy) - Miori M; Matteotti L (Forest@, 2007)
The project’s aim was to locate the wooden areas suitable for beekeeping activities. This has been possible thanks to the use of a multi-parametric model. This permits to define, for each of 85 forestal types of Trentino, the suitability for the production of nectar, bee bread and honeydew. According to the results, forestal types have been divided into 4 productivity classes. Datas have been reprocessed with GIS methodology so that high and medium productivity areas have been mapped. Following, new parameters have been introduced (distance from roads, slope, exposure) in order to highlight in the map the economically most important areas for beekeeping activities. In the next stage the apiaries’ position in the examined areas have been registered with the GPS. These registrations have been used in order to compare the theoretical results with the actual beekeeping activities’ distribution. The experimental stage showed that this methodology represents an useful tool to support beekeeping and, more in general, forest planning.